TIER 2: A Warm Welcomel or A Cold Reality?. Issue 1 (March 2019) - Stagnell, Sami; Bhatti, Mohamed Asim; Shembesh, Tarik; Patel, Nikki; Shah, Samit
Since the introduction of the 2006 NHS dental contract, various waiting list initiatives and the subsequent release of NHS commissioning guidance for dental services, there has been a remarkable and rapid shift towards the provision of intermediate services within the profession. The complexity surrounding those non-specialist providers working within these services has lead to much confusion and the further development of competencies required to work within these settings. This paper focuses on explaining and exploring the topics that arise from an area that has attracted much discussion and debate.